Grafting strategies for the synthesis of active DNase I polymer biohybrids. (October 2018) - Kovaliov, Marina; Cohen-Karni, Devora; Burridge, Kevin A.; Mambelli, Dorian; Sloane, Samantha; Daman, Nicholas; Xu, Chen; Guth, Jared; Kenneth Wickiser, J.; Tomycz, Nestor; Page, Richard C.; Konkolewicz, Dominik; et al.
Graphical abstract: Highlights: Polymer conjugation strategy was studied to compare the impact on the biohybrids activity. The grafting-from reaction conditions resulted in deactivated DNase I. Only grafting polymers to DNase I yielded active conjugates. Polymer hybrids with DNase I rendered the protein stable to heat denaturation. Abstract: Protein polymer hybrids play an increasingly important role in therapeutics and biocatalysis. Synthesis of these biohybrids can be achieved by either the grafting-from or grafting-to strategy and are generally thought to be interchangeable. Therefore, when choosing between these two strategies the decision is usually based on polymer accessibility and purification preference. However, in this study, we demonstrated that the choice of the polymer ligation strategy played a significant role in the stability and bioactivity of the final hybrid. Our goal was to prepare a thermally stable DNase I polymer hybrid by utilizing either synthetic strategies. We found that the grafting-from strategy using reversible addition-fragmentation chain transfer polymerization (RAFT) or atom transfer radical polymerization (ATRP) yielded DNase I biohybrids with no activity. Control reactions were used to demonstrate inherent protein deactivation caused by the grafting-from conditions for either ATRP or RAFT polymerization. The grafting-to method yielded active and thermally stable DNase I biohybrids.